Pengaruh Gel Ekstrak Etanol Daun Pucuk Merah Terhadap Densitas Tulang Alveolar Tikus Wistar Paska Ekstraksi Gigi - Ita Febriani; Risyandi anwar; Ika Rachmawati (SONDE (Sound of Dentistry), 2025)
Tooth extraction is the process of removing teeth from the alveolar bone and will result in damage to hard and soft tissue. The healing process after tooth extraction can be accelerated by administering drugs, for example dexamethasone, but this drug has side effects. The aim of this study was to determine the effect of ethanol extract gel from red shoot leaves on the alveolar bone density of Wistar rats after tooth extraction. This research is an experimental laboratory, with a posttest only control group research design. The samples in this study were 25 male Wistar rats which were divided into 2 control groups given povidone iodine and gel base, and 3 treatment groups given red shoot leaf ethanol extract gel with concentrations of 2%, 4% and 6%. On the 30th day, Wistar rats were euthanized and alveolar bone samples were taken, radiographs were taken using dental x-ray and bone density was assessed using Image-J. This study shows a p value of0.000 (p < 0.005), meaning that there are at least two groups with significantly different average alveolar bone densities. The highest average alveolar bone density value was in the group (K3) which was given 6% red shoot leaf ethanol extract gel. The conclusion of the research shows that administration of red shoot leaf ethanol extract gel with a concentration of 6% can increase the alveolar bone density of Wistar rats after tooth extraction.